Long-term Results of Arthroscopic Repair of Full-Thickness Traumatic Rotator Cuff Tears in Active Duty Military Patients Under the Age of 40 Years. Issue 10 (August 2022) - Scanaliato, John P.; Eckhoff, Michael D.; Dunn, John C.; Czajkowski, Hunter; Fink, Walter A.; Parnes, Nata
Background: Arthroscopic rotator cuff repair is an effective procedure through which to decrease pain and increase strength, with favorable long-term outcomes demonstrated in older patient populations with full-thickness rotator cuff tears. The long-term outcomes after this procedure in younger, higher-demand patients, however, is not as clearly defined. Purpose: To report on the long-term outcomes after arthroscopic rotator cuff repair of traumatic full-thickness rotator cuff tears in active duty military patients under the age of 40 years at the time of surgery. Study Design: Case series; Level of evidence, 4. Methods: Preoperative, midterm, and final evaluations were collected, including scores on the visual analog scale for pain, Single Assessment Numeric Evaluation, and American Shoulder and Elbow Surgeons shoulder form. A total of 42 patients were screened for inclusion: 3 underwent additional surgical procedures on the operative shoulder and 2 were lost to follow-up, leaving 37 patients with mean follow-up of 104.51 months available for analysis. A subgroup analysis was performed comparing outcomes between patients with Southern California Orthopaedic Institute grade 1 or 2 tears and those with grade 3 or 4 tears. Results: At final follow-up, pain per the visual analog scale decreased to 1.16 from 8.03 ( P < .0001); the Single Assessment Numeric Evaluation score increased to 87.32 from 48.24 ( P < .0001); and the American Shoulder and Elbow Surgeons score increased to 88.68 from 41.00 ( P < .0001). There was no statistically significant difference in outcome scores or range of motion between midterm and final follow-up. Improvement in outcome scores and range of motion at final follow-up did not vary between patients with small and large tears. Of 42 patients, 37 (88.1%) were able to return to full unrestricted active duty and sporting activity, while 5 (11.9%) were medically separated from the military. Conclusion: Active duty military patients under the age of 40 years with traumatic full-thickness rotator cuff tears had statistically and clinically significant increases in outcome scores and decreases in pain after arthroscopic rotator cuff repair at long-term follow-up.